Faculty views of CBE, self‐efficacy, and institutional support: An exploratory study. Issue 4 (26th September 2021) - Prokes, Christopher; Lowenthal, Patrick R.; Snelson, Chareen; Rice, Kerry
Abstract: Competency‐based education (CBE) is essentially an approach to teaching and learning featuring flexible pacing, robust competencies, and an emphasis on student completion. CBE differs from traditional education that focuses instead more on seat time and credit hours. Though CBE has existed on college campuses in many forms, faculty are often inexperienced in teaching CBE. Facing growing demands for CBE, institutions must find ways to prepare faculty to take part in CBE. This mixed methods study explored faculty views of CBE, their self‐efficacy, and beliefs about support mechanisms needed for those teaching and delivering CBE. Findings suggest faculty have mixed though balanced views of CBE, generally high self‐efficacy due to the importance of mastery experiences, and believe in the importance of specific learning opportunities in an environment built on collaboration to ensure CBE faculty are supported and can thrive. Findings can help institutions with CBE or those considering it to support faculty and ensure they are trained in teaching courses in this modality.